A silver-Ti3SiC2 electrical contact material and preparation method thereof

By designing the Ti3SiC2 skeleton and three-dimensional interpenetrating structure in the silver-Ti3SiC2 electrical contact material, the volume fraction of Ti3SiC2 is improved and the hot press sintering and melt impregnation process is adopted, the problem of low strength and hardness of the existing materials is solved, and high conductivity and excellent mechanical properties are achieved.

CN114724871BActive Publication Date: 2025-05-02INST OF METAL RESEARCH - CHINESE ACAD OF SCI
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210312764.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-03-28
Publication Date
2025-05-02
Estimated Expiration
2042-03-28

AI Technical Summary

Technical Problem

The existing silver-MAX phase electrical contact materials have low strength and hardness due to the low ceramic content of reinforced phase, which limits the amount of reinforced phase addition and affects the conductivity of the material.

Method used

By designing Ti3SiC2 as the skeleton, the three-dimensional interpenetrating structure in which silver penetrates into the Ti3SiC2 skeleton, the silver and Ti3SiC2 skeletons are bicontinuous phases, increasing the volume fraction of Ti3SiC2 to 50-70%, and the silver-Ti3SiC2 electrical contact material is prepared by hot press sintering and melt infiltration processes.

Benefits of technology

On the basis of maintaining high conductivity, the mechanical properties of the material are significantly improved, including Vickers hardness, bending strength and wear resistance, and the process is simple and industrially produced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114724871B_ABST
    Figure CN114724871B_ABST
Patent Text Reader

Abstract

The present invention relates to a silver-Ti3SiC2 electrical contact material and a preparation method thereof, and relates to the technical field of silver-based electrical contact materials. The main technical solution adopted is as follows: A silver-Ti3SiC2 electrical contact material has a three-dimensional interpenetrating structure with Ti3SiC2 as the skeleton and silver infiltrating into the Ti3SiC2 skeleton, and silver and the Ti3SiC2 skeleton are a bicontinuous phase; wherein, in the silver-Ti3SiC2 electrical contact material, the volume fraction of Ti3SiC2 is 50-70%; wherein, the Vickers hardness of the silver-Ti3SiC2 electrical contact material is greater than 1.9 GPa, preferably greater than 2 GPa; the flexural strength of the silver-Ti3SiC2 electrical contact material is not less than 520 MPa, preferably greater than 630 MPa; the electrical conductivity of the silver-Ti3SiC2 electrical contact material is greater than 5 MS / m, preferably greater than 6.5 MS / m. The present invention is mainly used to ensure the electrical conductivity of the silver-Ti3SiC2 electrical contact material and also endow the silver-Ti3SiC2 electrical contact material with good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of silver-based electrical contact materials, in particular to a silver-Ti3SiC2 electrical contact material and a preparation method thereof. Background Art

[0002] Electrical contact materials are key materials for the contact parts of electrical appliances (such as switches, relays, starters, etc.) that are responsible for on / off control and load current in circuits. Among them, silver-based electrical contact materials have the advantages of excellent conductivity and resistance to welding, small and stable contact resistance, and are widely used in circuit breakers and contactors in various light and heavy loads of high and low voltage household, automotive, and aerospace electrical appliances.

[0003] The silver-MAX phase electrical contact materials in the prior art are mainly composite materials prepared by powder metallurgy, for example:

[0004] The first prior art provides a method for preparing a Ti3SiC2 reinforced Ag-based electrical contact material. The main scheme is: Ti3SiC2 powder and Ag powder are mixed and ball-milled in proportion, cold-pressed into a blank and then sintered at high temperature to prepare a Ti3SiC2 reinforced Ag-based electrical contact composite material with uniform structure, high density and excellent conductivity.

[0005] The second prior art provides a method for preparing an Ag / MAX electrical contact material. The main scheme is: Ag grain refinement, lamellar MAX phase stratification and directional arrangement, dense and anisotropic Ag / MAX phase electrical contact material is prepared by combining powder metallurgy with equal channel angular extrusion.

[0006] The third prior art provides an Ag / Ti3SiC2 electrical contact material and a preparation method thereof. The main scheme is: silver-plated Ti3SiC2 powder is added to a silver matrix by a powder metallurgy method to prepare a silver-based electrical contact material, and the actual product is obtained by hot extrusion molding, rolling or drawing, and mechanical processing.

[0007] Here, the composite material prepared by powder metallurgy: the MAX phase is usually dispersed in the silver matrix as a reinforcing phase, and there is no spatial connection between them, which leads to no current conduction between the conductive MAX phases. The current path mainly consists of two parts: one is the silver matrix; the other is silver-MAX-silver. The current conduction at the interface will lead to an increase in the resistance of the material. In addition, the matrix metal silver provides high electrical conductivity for the composite material, but its softness leads to poor mechanical properties, and the MAX reinforcing phase is used to improve the mechanical properties of the material, but the electrical conductivity of the reinforcing phase material is low. Increasing the amount of addition will seriously affect the conductivity of the composite material, which limits the addition of the reinforcing phase (the volume fraction of the reinforcing phase is low).

[0008] In summary, in order to ensure the electrical conductivity, the silver-MAX phase electrical contact material in the prior art has a low content of reinforcing phase ceramics, which causes the electrical contact material to have problems such as low strength and hardness. Summary of the invention

[0009] In view of this, the present invention provides a silver-Ti3SiC2 electrical contact material and a preparation method thereof, the main purpose of which is to ensure the electrical conductivity of the silver-Ti3SiC2 electrical contact material while also making the silver-Ti3SiC2 electrical contact material have better mechanical properties.

[0010] In order to achieve the above object, the present invention mainly provides the following technical solutions:

[0011] On the one hand, an embodiment of the present invention provides a silver-Ti3SiC2 electrical contact material, wherein the silver-Ti3SiC2 electrical contact material is a three-dimensional interpenetrating structure with Ti3SiC2 as a skeleton and silver infiltrated into the Ti3SiC2 skeleton, and silver and the Ti3SiC2 skeleton are a dual continuous phase; wherein, in the silver-Ti3SiC2 electrical contact material, the volume fraction of Ti3SiC2 is 50-70%, and the rest is silver;

[0012] Among them, the Vickers hardness of the silver-Ti3SiC2 electrical contact material is not less than 1.9GPa, preferably greater than 2GPa; the bending strength of the silver-Ti3SiC2 electrical contact material is greater than 520MPa, preferably greater than 630MPa; the electrical conductivity of the silver-Ti3SiC2 electrical contact material is greater than 5MS / m, preferably greater than 6.5MS / m.

[0013] Preferably, if the Ti3SiC2 skeleton is made of nano-scale Ti3SiC2 powder, then in the silver-Ti3SiC2 electrical contact material: the volume fraction of Ti3SiC2 is 59-67%; if the Ti3SiC2 skeleton is made of micron-scale Ti3SiC2 powder, then in the silver-Ti3SiC2 electrical contact material: the volume fraction of Ti3SiC2 is 59-70%.

[0014] Preferably, the Ti3SiC2 skeleton is made of nano-scale Ti3SiC2 powder; wherein the particle size of the nano-scale Ti3SiC2 powder is 300-1600nm, preferably 600-940nm, and more preferably 700-730nm. Preferably, the density of the silver-Ti3SiC2 electrical contact material is 6.52-7.33g / cm 3 ; and / or the Vickers hardness of the silver-Ti3SiC2 electrical contact material is 2.06-3.36GPa; and / or the bending strength of the silver-Ti3SiC2 electrical contact material is 633-778MPa; and / or the fracture toughness K of the silver-Ti3SiC2 electrical contact materialIC The value is 14-16MPa·m 1 / 2 ; and / or the electrical conductivity of the silver-Ti3SiC2 electrical contact material is 6.7-7.6MS / m; and / or the friction coefficient of the silver-Ti3SiC2 electrical contact material is 0.28-0.30; and / or the wear rate of the silver-Ti3SiC2 electrical contact material is 7.6-17.5×10 -6 mm / (N·m).

[0015] Preferably, the Ti3SiC2 skeleton is made of micron-sized Ti3SiC2 powder; wherein the particle size of the micron-sized Ti3SiC2 powder is 5-66.5 microns, preferably 24-24.5 microns. Preferably, the density of the silver-Ti3SiC2 electrical contact material is 6.35-6.97 g / cm 3 ; and / or the Vickers hardness of the silver-Ti3SiC2 electrical contact material is 1.99GPa-2.93GPa; and / or the bending strength of the silver-Ti3SiC2 electrical contact material is 520-568MPa; and / or the fracture toughness K of the silver-Ti3SiC2 electrical contact material IC The value is 9.3-12.84MPa·m 1 / 2 ; and / or the electrical conductivity of the silver-Ti3SiC2 electrical contact material is 5.3-6.91MS / m; and / or the friction coefficient of the silver-Ti3SiC2 electrical contact material is 0.30-0.32; and / or the wear rate of the silver-Ti3SiC2 electrical contact material is 3.4-16.7×10 -6 mm / (N·m).

[0016] On the other hand, an embodiment of the present invention further provides a method for preparing any of the above silver-Ti3SiC2 electrical contact materials, which comprises the following steps:

[0017] Preparation of Ti3SiC2 skeleton steps: filling Ti3SiC2 powder into a mold, and sintering in a protective atmosphere or vacuum conditions to obtain a Ti3SiC2 skeleton;

[0018] Melt infiltration treatment steps: The Ti3SiC2 skeleton and the silver block are subjected to melt infiltration treatment, and after a set time, a silver-Ti3SiC2 electrical contact material is obtained.

[0019] Preferably, in the step of preparing the Ti3SiC2 skeleton: the sintering temperature is 800-1500°C, the sintering pressure is 0-2t, and the sintering time is 1-3h.

[0020] Preferably, the step of preparing the Ti3SiC2 skeleton is carried out in a vacuum hot pressing furnace.

[0021] Preferably, the infiltration treatment step is specifically as follows: placing the Ti3SiC2 skeleton and the silver block in a container; heating the container under a protective atmosphere or vacuum conditions to an infiltration treatment temperature, and keeping the temperature at the infiltration treatment temperature for a set time, and obtaining the silver-Ti3SiC2 electrical contact material after cooling.

[0022] Preferably, the infiltration treatment temperature is 1000-1400°C, preferably 1200°C; and / or

[0023] Preferably, the set time is 1-2 hours, preferably 2 hours.

[0024] Compared with the prior art, the silver-Ti3SiC2 electrical contact material and the preparation method thereof of the present invention have at least the following beneficial effects:

[0025] On the one hand, the silver-Ti3SiC2 electrical contact material provided by the embodiment of the present invention is a three-dimensional interpenetrating structure with Ti3SiC2 as the skeleton and silver infiltrated into the Ti3SiC2 skeleton, and the silver and the Ti3SiC2 skeleton are a dual continuous phase; wherein, in the silver-Ti3SiC2 electrical contact material, the volume fraction of Ti3SiC2 is 50-70%; wherein, the Vickers hardness of the silver-Ti3SiC2 electrical contact material is greater than 2.2GPa, the bending strength is greater than 500MPa, and the electrical conductivity is greater than 5MS / m. Therefore, the silver-Ti3SiC2 electrical contact material provided by the present invention has excellent mechanical properties on the basis of ensuring electrical conductivity. In addition, the silver-Ti3SiC2 electrical contact material provided by the embodiment of the present invention also has excellent wear resistance.

[0026] Furthermore, the Ti3SiC2 skeleton is made of nano-scale powder or micron-scale powder. Under the condition of the same Ti3SiC2 content, the silver-Ti3SiC2 electrical contact material made of nano-scale powder has a finer and more uniform structure, as well as better mechanical properties, wear resistance and higher conductivity.

[0027] On the other hand, the embodiment of the present invention also provides a method for preparing the above-mentioned silver-Ti3SiC2 electrical contact material, which is mainly prepared by hot pressing sintering and melt infiltration process, wherein the skeleton porosity can be controlled by controlling the skeleton sintering temperature, thereby controlling the content of the two phases in the composite material, thereby adjusting the mechanical properties of the silver-Ti3SiC2 electrical contact material. In addition, the preparation process is simple and can be industrialized.

[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a process flow chart of preparing a silver-Ti3SiC2 electrical contact material provided by an embodiment of the present invention;

[0030] Figure 2 This is the macroscopic morphology of the sample of the silver-Ti3SiC2 electrical contact material prepared in Example 1 of the present invention;

[0031] Figure 3 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 1 of the present invention;

[0032] Figure 4 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 2 of the present invention;

[0033] Figure 5 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 3 of the present invention;

[0034] Figure 6 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 4 of the present invention;

[0035] Figure 7 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 5 of the present invention;

[0036] Figure 8 is a microstructure diagram of the silver-Ti3SiC2 electrical contact material prepared in Example 6 of the present invention;

[0037] Fig. 9 It is the curve of the hardness of silver-Ti3SiC2 electrical contact material changing with the Ti3SiC2 content;

[0038] Fig.10 It is the curve of the conductivity of silver-Ti3SiC2 electrical contact material changing with the Ti3SiC2 content;

[0039] Fig.11 It is the curve of the bending strength of silver-Ti3SiC2 electrical contact material changing with the Ti3SiC2 content;

[0040] Fig.12 This is the curve of the fracture toughness of silver-Ti3SiC2 electrical contact material changing with the Ti3SiC2 content. DETAILED DESCRIPTION

[0041] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention application are described in detail below in conjunction with the accompanying drawings and preferred embodiments. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures, or characteristics in one or more embodiments may be combined in any suitable form.

[0042] In order to ensure the electrical conductivity of the prior art, the content of the reinforcing phase ceramic is low, resulting in technical problems such as low strength and hardness of the silver-Ti3SiC2 electrical contact material. Here, the inventors of the present invention hope to increase the ceramic Ti3SiC2 content through structural design without significantly reducing the electrical conductivity of the material, thereby improving the mechanical properties of the material.

[0043] The existing silver-Ti3SiC2 electrical contact materials are mainly prepared by powder metallurgy. In these materials, the Ti3SiC2 phase is usually dispersed in the silver matrix as a reinforcing phase, and there is no spatial connection between them, which leads to no current conduction between the conductive Ti3SiC2 phases (the inventors found that the current path of the material is mainly composed of two parts: ① silver matrix; ② silver-Ti3SiC2-silver. The current conduction at the interface will lead to an increase in the resistance of the material). Here, the inventors found that by designing a three-dimensional interpenetrating structure of the Ti3SiC2 phase, the interface in the material current conduction process can be reduced, thereby improving the conductivity; on the basis of appropriately increasing the content of the reinforcing phase, the conductivity can also be ensured. In addition, the three-dimensional interpenetrating structure of the reinforcing phase will also further improve the mechanical properties of the composite material. This structural design can make up for the deficiencies in mechanical properties such as hardness and strength of traditional silver-Ti3SiC2 electrical contact materials.

[0044] The specific scheme of the present invention is as follows:

[0045] The embodiment of the present invention provides a silver-Ti3SiC2 electrical contact material. The silver-Ti3SiC2 electrical contact material is a three-dimensional interpenetrating structure with micron-scale or nano-scale Ti3SiC2 ceramic powder as the skeleton, silver infiltrates the skeleton, and silver and the Ti3SiC2 skeleton are a dual continuous phase; wherein the volume fraction of the Ti3SiC2 is 50-70%, preferably 53-69%, and the rest is silver.

[0046] Among them, the preparation method of the silver-Ti3SiC2 electrical contact material (specific preparation process see Figure 1 ), which comprises the following steps:

[0047] 1) Steps for preparing a Ti3SiC2 skeleton: Fill Ti3SiC2 powder into a mold and perform sintering treatment in a protective atmosphere or vacuum conditions to obtain a Ti3SiC2 skeleton.

[0048] In this step: the sintering temperature is 800-1500° C., the sintering pressure is 0-2t, and the sintering time is 1-3h.

[0049] 2) Melt infiltration treatment step: The Ti3SiC2 skeleton and the silver block are subjected to melt infiltration treatment, and after a set time, a silver-Ti3SiC2 electrical contact material is obtained.

[0050] The specific steps are as follows: placing a Ti3SiC2 skeleton and a silver block in a container; heating the container under a protective atmosphere or vacuum conditions to an infiltration treatment temperature, and maintaining the temperature at the infiltration treatment temperature for a set time, and after cooling, obtaining a silver-Ti3SiC2 electrical contact material.

[0051] Preferably, the infiltration treatment temperature is 1000-1400°C, preferably 1200°C; the set time is 1-2h, preferably 2h.

[0052] The following is further described by specific examples:

[0053] Example 1

[0054] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0055] 1) Preparation of Ti3SiC2 skeleton step: about 85g of nano Ti3SiC2 powder with a particle size of about 700nm is filled into a mold (50mm between the molds), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 900°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0056] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 49.8 mm (shrinkage after sintering), a thickness of 27.2 mm, and a mass of 84.06 g.

[0057] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0058] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and about 200g of silver block in a container; heat the container to 1200°C under pure argon protection or vacuum conditions, and keep it at 1200°C for 2h, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0059] The macroscopic morphology of the sample of silver-Ti3SiC2 electrical contact material prepared in this embodiment is as follows: Figure 2 As shown. Figure 2 It can be seen that the surface of the silver-Ti3SiC2 electrical contact material presents a metallic luster and has no obvious defects; wherein, the diameter of the silver-Ti3SiC2 electrical contact material sample is about 47 mm.

[0060] Example 2

[0061] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0062] 1) Preparation of Ti3SiC2 skeleton step: about 70g of nano Ti3SiC2 powder with a particle size of about 700nm is filled into a mold (mold diameter is 50mm), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 1200°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0063] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 46.8 mm (shrinkage after sintering), a thickness of 20.0 mm, and a mass of 67.08 g.

[0064] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0065] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and about 200g of silver block in a container; heat the container to 1200°C in a pure argon protective atmosphere or under vacuum conditions, and keep it at 1200°C for 2h, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0066] Example 3

[0067] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0068] 1) Preparation of Ti3SiC2 skeleton step: about 62g of nano Ti3SiC2 powder with a particle size of about 700nm is filled into a mold (mold diameter is 50mm), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 1400°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0069] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 40.7 mm (shrinkage after sintering), a thickness of 16.4 mm, and a mass of 60.96 g.

[0070] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0071] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and about 200g of silver block in a container; heat the container to 1200°C in a pure argon protective atmosphere or under vacuum conditions, and keep it at 1200°C for 2h, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0072] Example 4

[0073] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0074] 1) Preparation of Ti3SiC2 skeleton: about 133g of Ti3SiC2 powder with a particle size of 24 microns is filled into a mold (mold diameter is 50mm), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 900°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0075] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 49.7 mm (shrinkage after sintering), a thickness of 26.9 mm, and a mass of 131.42 g.

[0076] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0077] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and about 200g of silver block in a container; heat the container to 1200°C in a pure argon protective atmosphere or under vacuum conditions, and keep it at 1200°C for 2h, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0078] Example 5

[0079] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0080] 1) Preparation of Ti3SiC2 skeleton: about 140g of Ti3SiC2 powder with a particle size of 24 microns is filled into a mold (mold diameter is 50mm), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 1200°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0081] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 48.3 mm (shrinkage after sintering), a thickness of 26.1 mm, and a mass of 137.53 g.

[0082] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0083] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and about 200g of silver block in a container; heat the container to 1200°C in a pure argon protective atmosphere or under vacuum conditions, and keep it at 1200°C for 2h, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0084] Example 6

[0085] This embodiment prepares a silver-Ti3SiC2 electrical contact material, and the specific steps are as follows:

[0086] 1) Preparation of Ti3SiC2 skeleton: about 170g of Ti3SiC2 powder with a particle size of 24 microns is filled into a mold (mold diameter is 50mm), and then placed in a hot pressing sintering furnace, and sintered under an argon protective atmosphere to obtain a Ti3SiC2 skeleton. The sintering temperature is 1400°C, the sintering time is 1 hour, and the sintering pressure is 2t.

[0087] It should be noted here that the obtained Ti3SiC2 skeleton has a diameter of 46.3 mm (shrinkage after sintering), a thickness of 32.1 mm, and a mass of 167.7 g.

[0088] The Ti3SiC2 skeleton was cut into 8 mm thick discs and then infiltrated (the shrinking shape was irregular, and infiltration was performed after cutting so that the final silver-Ti3SiC2 electrical contact material sample could be more regular).

[0089] 2) Melt infiltration treatment step: Place the Ti3SiC2 skeleton and the silver block in a container; Heat the container to 1200°C in a pure argon protective atmosphere or under vacuum conditions, and keep it at 1200°C for 2 hours, and obtain the silver-Ti3SiC2 electrical contact material after cooling.

[0090] 1. The microstructure of the silver-Ti3SiC2 electrical contact materials prepared in Examples 1-6 is characterized as follows:

[0091] The microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 1 is as follows Figure 3 As shown; the microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 2 is as shown Figure 4 As shown; the microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 3 is as shown Figure 5 As shown; the microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 4 is as shown Figure 6 The microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 5 is shown in Figure 7 As shown; the microstructure of the silver-Ti3SiC2 electrical contact material prepared in Example 6 is as shown Figure 8 shown.

[0092] from Figure 3-Figure 8 It can be seen that: (1) the silver and Ti3SiC2 in the silver-Ti3SiC2 electrical contact materials prepared in Examples 1-6 are interpenetrating in three-dimensional space. (2) Under the same magnification, the silver-Ti3SiC2 electrical contact material prepared using nanopowder Ti3SiC2 has a finer microstructure, and its structure is more uniform, and the corresponding mechanical properties are improved to a higher level.

[0093] 2. The performance of the silver-Ti3SiC2 electrical contact materials prepared in Examples 1-6 was tested. The test structures are shown in Tables 1 and 2.

[0094] Table 1

[0095] Example 1 Example 2 Example 3 density 7.32 6.78 6.52 Volume fraction% 53.1 62.3 66.6 Vickers hardness(GPa) 2.41±0.02 2.9±0.04 3.16±0.04 Bending strength(MPa) 755.31±18.61 678.40±14.10 687.35±27.88 <![CDATA[Fracture toughness K1C value (MPa·m 1 / 2 )]]> 15.14±0.68 14.99±0.94 14.64±0.15 Conductivity (MS / m) 7.41±0.11 7.28±0.22 6.95±0.22 Friction coefficient 0.29 0.28 0.29 Wear rate (mm / N·m) <![CDATA[14.64±0.44×10 -6 ]]> <![CDATA[10.82±0.78×10 -6 ]]> <![CDATA[10.15±0.39×10 -6 ]]>

[0096] Table 2

[0097] Example 4 Example 5 Example 6 density 6.97 6.73 6.35 Volume fraction% 59.1 63.0 69.4 Vickers hardness(GPa) 2.35±0.06 2.52±0.05 2.61±0.10 Bending strength(MPa) 529.97±9.46 531.32±5.62 544.42±19.97 <![CDATA[Fracture toughness K1C value (MPa·m 1 / 2 )]]> 11.68±1.00 11.24±0.73 10.59±1.25 Conductivity (MS / m) 6.58±0.20MS / m 5.99±0.10 5.50±0.16 Friction coefficient 0.31 0.30 0.32 Wear rate (mm / N·m) <![CDATA[5.00±0.28×10 -6 ]]> <![CDATA[8.67±0.87×10 -6 ]]> <![CDATA[11.07±1.41×10 -6 ]]>

[0098] Note: The density of the silver-Ti3SiC2 electrical contact material of this embodiment is measured by the Archimedean drainage method, and then the volume fraction of Ti3SiC2 in the silver-Ti3SiC2 electrical contact material is deduced based on the density. The silver-Ti3SiC2 electrical contact material is subjected to a three-point bending test to test the bending strength. The electrical conductivity of the silver-Ti3SiC2 electrical contact material is measured by an eddy current conductivity meter. The friction coefficient and wear rate of the silver-Ti3SiC2 electrical contact material are measured by a friction and wear test.

[0099] 3. Fig. 9 : is a curve showing the change of the hardness of the silver-Ti3SiC2 electrical contact material with the Ti3SiC2 content. Among them, the hardness of the silver-Ti3SiC2 electrical contact material prepared using micron powder and nano powder Ti3SiC2 in the embodiment of the present invention shows an upward trend with the increase of Ti3SiC2 content. And under the condition of the same Ti3SiC2 content, the silver-Ti3SiC2 electrical contact material prepared using nano powder Ti3SiC2 has a higher hardness.

[0100] In addition, the processes used in other documents, such as pressureless sintering and spark plasma sintering, generally have low Ti3SiC2 contents in the silver-Ti3SiC2 electrical contact materials prepared by these two processes, but in the part with higher Ti3SiC2 contents, the silver-Ti3SiC2 electrical contact materials prepared by the process (sintering + melt infiltration) of the embodiment of the present invention have higher hardness.

[0101] 4. Fig.10 3 is a curve showing the change of the conductivity of the silver-Ti3SiC2 electrical contact material with the Ti3SiC2 content. In particular, the conductivity of the silver-Ti3SiC2 electrical contact material prepared using micron powder and nanopowder Ti3SiC2 in the embodiment of the present invention shows a downward trend with the increase of Ti3SiC2 content, and when the Ti3SiC2 content is the same, the silver-Ti3SiC2 electrical contact material prepared using nanopowder Ti3SiC2 has a higher conductivity.

[0102] In addition, the processes used in other documents, such as pressureless sintering and spark plasma sintering, generally have low Ti3SiC2 contents in the silver-Ti3SiC2 electrical contact materials prepared by these two processes, but in the part with higher Ti3SiC2 contents, the silver-Ti3SiC2 electrical contact materials prepared by the process (sintering + melt infiltration) of the embodiment of the present invention have higher electrical conductivity.

[0103] 5. Fig.11: is a curve showing the change of the bending strength of the silver-Ti3SiC2 electrical contact material with the Ti3SiC2 content. Among them, the bending strength of the silver-Ti3SiC2 electrical contact material prepared using nano-powder Ti3SiC2 in the embodiment of the present invention shows a downward trend as the Ti3SiC2 content increases, and the bending strength of the silver-Ti3SiC2 electrical contact material prepared using micron-powder Ti3SiC2 shows an upward trend as the Ti3SiC2 content increases. Moreover, under the condition of the same Ti3SiC2 content, the bending strength of the silver-Ti3SiC2 electrical contact material prepared using nano-powder Ti3SiC2 is higher.

[0104] 6. Fig.12 It is a curve of the fracture toughness value of the silver-Ti3SiC2 electrical contact material as a function of the Ti3SiC2 content. Among them, the fracture toughness of the silver-Ti3SiC2 electrical contact material prepared using micron powder and nano powder Ti3SiC2 in the embodiment of the present invention both shows a downward trend as the Ti3SiC2 content increases. And when the Ti3SiC2 content is the same, the silver-Ti3SiC2 electrical contact material prepared using nano powder Ti3SiC2 has a higher fracture toughness value.

[0105] It should be noted here that:

[0106] ① The size of the reinforcement phase particles currently used is at the micron level, but the embodiment of the present invention proposes that when the size of the reinforcement phase reaches the nanometer level, the interface between the two phases becomes complex, so that the properties of the silver-Ti3SiC2 electrical contact material will change, and the size effect will further improve the performance of the material.

[0107] ② In traditional silver-Ti3SiC2 electrical contact materials, the content of reinforcing phase is often low, and because the traditional preparation process is mainly based on powder metallurgy, the reinforcing phase is randomly distributed in the silver matrix without mutual connection. Here, it is proposed to increase the content of reinforcing phase and establish a three-dimensional connection between the reinforcing phases (design of three-dimensional interpenetrating structure), and the comprehensive performance of the composite material will be improved after hot pressing and sintering the reinforcing phase Ti3SiC2.

[0108] ③ The hot pressing sintering + melt infiltration process proposed in the embodiment of the present invention can control the skeleton porosity of the material by controlling the skeleton sintering temperature, and then control the content of the two phases in the silver-Ti3SiC2 electrical contact material, thereby controlling the mechanical properties of the material.

[0109] The silver-Ti3SiC2 electrical contact material prepared by the embodiment of the present invention achieves an increase in the content of the reinforcing phase, and the Ti3SiC2 content reaches 50-70 vol.%. Compared with electrical contact materials with the same Ti3SiC2 content prepared by other processes, the silver-Ti3SiC2 electrical contact material prepared by the implementation of the present invention has high electrical conductivity, and its hardness and mechanical properties are greatly improved. For the silver-Ti3SiC2 electrical contact material prepared by the embodiment of the present invention, the silver-Ti3SiC2 electrical contact material prepared using nano-powder Ti3SiC2 is also superior to the silver-Ti3SiC2 electrical contact material prepared using micron powder Ti3SiC2 in terms of performance.

[0110] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A silver-Ti3SiC2 electrical contact material, characterized in that: The silver-Ti3SiC2 electrical contact material is a three-dimensional interpenetrating structure with Ti3SiC2 as the skeleton and silver infiltrated into the Ti3SiC2 skeleton, and the silver and the Ti3SiC2 skeleton are a double continuous phase; wherein, in the silver-Ti3SiC2 electrical contact material, the volume fraction of the Ti3SiC2 is 50-70%, and the rest is silver; Wherein, the Vickers hardness of the silver-Ti3SiC2 electrical contact material is greater than 1.9GPa; the bending strength of the silver-Ti3SiC2 electrical contact material is not less than 520MPa; the electrical conductivity of the silver-Ti3SiC2 electrical contact material is greater than 5MS / m; The preparation method of the silver-Ti3SiC2 electrical contact material comprises the following steps: Preparation of Ti3SiC2 skeleton step: filling Ti3SiC2 powder into a mold, and sintering in a protective atmosphere or vacuum to obtain a Ti3SiC2 skeleton; wherein the sintering temperature is 800-1500°C, the sintering pressure is greater than 0 and less than or equal to 2t, and the sintering time is 1-3h; Melt infiltration treatment step: melt infiltration treatment is performed on the Ti3SiC2 skeleton and the silver block, and after a set time, a silver-Ti3SiC2 electrical contact material is obtained; Wherein, the Ti3SiC2 skeleton is made of nano-sized Ti3SiC2 powder or micron-sized Ti3SiC2 powder; When the Ti3SiC2 skeleton is made of nano-scale Ti3SiC2 powder, in the silver-Ti3SiC2 electrical contact material: the volume fraction of Ti3SiC2 is 59-67%; the particle size of the nano-scale Ti3SiC2 powder is 300-1600nm; When the Ti3SiC2 skeleton is made of micron-sized Ti3SiC2 powder, in the silver-Ti3SiC2 electrical contact material: the volume fraction of Ti3SiC2 is 59-70%; and the particle size of the micron-sized Ti3SiC2 powder is 5-66.5 microns.

2. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The Vickers hardness of the silver-Ti3SiC2 electrical contact material is greater than 2 GPa.

3. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The bending strength of the silver-Ti3SiC2 electrical contact material is greater than 630 MPa.

4. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The electrical conductivity of the silver-Ti3SiC2 electrical contact material is greater than 6.5MS / m.

5. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The particle size of the nano-scale Ti3SiC2 powder is 600-940nm.

6. The silver-Ti3SiC2 electrical contact material according to claim 5, characterized in that: The particle size of the nano-scale Ti3SiC2 powder is 700-730nm.

7. The silver-Ti3SiC2 electrical contact material according to any one of claims 1, 5 and 6, characterized in that: The density of the silver-Ti3SiC2 electrical contact material is 6.52-7.33 g / cm 3 ; and / or The Vickers hardness of the silver-Ti3SiC2 electrical contact material is 2.06-3.36 GPa; and / or The bending strength of the silver-Ti3SiC2 electrical contact material is 633-778 MPa; and / or The fracture toughness K of the silver-Ti3SiC2 electrical contact material IC The value is 14-16MPa·m 1 / 2 ; and / or The electrical conductivity of the silver-Ti3SiC2 electrical contact material is 6.7-7.6MS / m; and / or The friction coefficient of the silver-Ti3SiC2 electrical contact material is 0.28-0.30; and / or The wear rate of the silver-Ti3SiC2 electrical contact material is 7.6-17.5×10 -6 mm / N·m.

8. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The particle size of the micron-sized Ti3SiC2 powder is 24-24.5 microns.

9. The silver-Ti3SiC2 electrical contact material according to claim 1 or 8, characterized in that: The density of the silver-Ti3SiC2 electrical contact material is 6.35-6.97 g / cm 3 ; and / or The Vickers hardness of the silver-Ti3SiC2 electrical contact material is 1.99GPa-2.93GPa; and / or The bending strength of the silver-Ti3SiC2 electrical contact material is 520-568MPa; and / or The fracture toughness K of the silver-Ti3SiC2 electrical contact material IC The value is 9.3-12.84MPa·m 1 / 2 ; and / or The electrical conductivity of the silver-Ti3SiC2 electrical contact material is 5.3-6.91MS / m; and / or The friction coefficient of the silver-Ti3SiC2 electrical contact material is 0.30-0.32; and / or The wear rate of the silver-Ti3SiC2 electrical contact material is 3.4-16.7×10 -6 mm / N·m.

10. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The step of preparing the Ti3SiC2 skeleton is carried out in a vacuum hot pressing furnace.

11. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The infiltration treatment steps are specifically: The Ti3SiC2 skeleton and the silver block are placed in a container; the container is heated in a protective atmosphere or vacuum conditions to an infiltration treatment temperature, and is kept at the infiltration treatment temperature for a set time, and the silver-Ti3SiC2 electrical contact material is obtained after cooling.

12. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The temperature of the infiltration treatment is 1000-1400°C.

13. The silver-Ti3SiC2 electrical contact material according to claim 12, characterized in that: The infiltration treatment temperature is 1200°C.

14. The silver-Ti3SiC2 electrical contact material according to claim 1, characterized in that: The setting time is 1-2h.

15. The silver-Ti3SiC2 electrical contact material according to claim 14, characterized in that: The set time is 2h.

Citation Information

Patent Citations

  • Ag / Ti3SiC2 electric contact material and manufacturing process

    CN101343700A

  • Silver-based composite material and preparation method thereof

    CN112974774A